Perceived control and coping strategies with organizational problems - Pociūtė-Kmeliauskienė, Vilmantė; Suslavičius, Antanas (Psichologija, 2001)
The goal our research was: to examine a link between different perceived control and organizational problem coping strategies, perceived as the most effective The method consists of two stages. In the first stage we have used Coping questionnaire (Carver, Scheier, 1989) that helped to divide workers into two groups: high perceived control and low perceived control. In the second stage we have used our original method: we have given organizational problem - situations and six coping strategies to each of them. Workers had to make the priority for the coping strategies according to their own behavior. The data of research supported our predictions. High perceived control workers choose problem - focused coping for organizational problems. Low perceived control workers choose emotion - focused coping strategies for organizational problems.